Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jvs.2013.11.095
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of abdominal branch vessel patency after bare-metal stenting of the thoracoabdominal aorta in a human ex vivo model of acute type B aortic dissection

Abstract: Bare-metal stenting in this model of acute type B aortic dissection was effective in true lumen reexpansion but induced a high (54.5%) rate of significant pressure drop in the visceral and renal arteries when they were supplied by the false lumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…After TEVAR, visceral and renal arteries perfused by the FL showed a significant pressure drop in 55% (12 of 22). 140 Autopsy and animal studies help to understand stentgraft performance and biomechanical aortic changes considerably. Rubin et al 109 reported a fatal case of retrograde AD after TEVAR plus balloon dilation for TBAD.…”
Section: Experimental Analyses Of Aortic Wall and Stent-graft Failuresmentioning
confidence: 99%
See 2 more Smart Citations
“…After TEVAR, visceral and renal arteries perfused by the FL showed a significant pressure drop in 55% (12 of 22). 140 Autopsy and animal studies help to understand stentgraft performance and biomechanical aortic changes considerably. Rubin et al 109 reported a fatal case of retrograde AD after TEVAR plus balloon dilation for TBAD.…”
Section: Experimental Analyses Of Aortic Wall and Stent-graft Failuresmentioning
confidence: 99%
“…137,138 In the development stage of TEVAR, Marty-Ané et al 139 reported from an in vivo canine study that complete dissection obliteration could be accomplished only when the entire length of the dissected aorta was treated, as otherwise a false channel continued to exist. 139 Faure et al 140 studied the efficiency of bare metal stenting in 15 human aortic ex vivo models and the impact on visceral and renal arterial patency. Reexpansion of the TL with FL collapse was achieved in all cases.…”
Section: Experimental Analyses Of Aortic Wall and Stent-graft Failuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Following, every pose-dependent virtual angioscopy image was created at runtime in MeVisLab using the Open Inventor library [7] from an aorta segmentation of a previous CT scan. The vessel appearance is based on ex vivo and in vivo angioscopies [8,9]. When requested by HoloLens, the last encoded virtual angioscopy image was sent from MeVis-Lab to the AR glasses via Wi-Fi using a remote procedure call (gRPC) [10].…”
Section: Methodsmentioning
confidence: 99%
“…The point of view of the catheter, which was incorporated in the initial version of the Nav EVAR prototype [28], was replaced with a virtual angioscopy implemented with Open Inventor library [29]. The appearance of the vessel wall follows that shown in ex vivo and in vivo angioscopies [30], [31].…”
Section: Methodsmentioning
confidence: 99%